A Qualitative Examination of Perceived Stigma and its Sources Among Adolescents Living With HIV in Western Kenya. (January 2022) - Callen, Grant; Chory, Ashley; Sang, Festus; Munyoro, Dennis; Aluoch, Josephine; Scanlon, Michael; Enane, Leslie; McHenry, Megan; Wools-Kaloustian, Kara; Apondi, Edith; Vreeman, Rachel
Introduction. Adolescents (10-19 years) living with HIV (ALWH) face unique challenges in controlling HIV long-term, including stigma and perception of stigma within their communities. Methods. We conducted a qualitative investigation of the sources of perceived HIV-related stigma with ALWH in western Kenya. Forty-six ALWH on ART, aware of their status, and engaged in care were enrolled. Interviews explored perceived stigma by probing the individuals and experiences that adolescents identify as causing or perpetuating their ongoing fears. Results. Participants (54% male, mean age 17.4) reported ongoing fears of stigmatization related to friends and peers not living with HIV. They described previous enacted and first-hand observations of stigma, most often occurring in pre-adolescence, by age mates or peers at school as the most common cause for their ongoing fears. Conclusions. Perceived stigma is prevalent among ALWH and develops from experiences in pre-adolescence. Anti-HIV stigma interventions addressing educators and children in school settings to combat perceived stigma at its source should be investigated.